Evaluation of the Rickettsemia relationships of Anaplasma marginale with agroecological and productive factors in double purpose cattle in flooded savannas of Arauca, Colombia - Salamanca Carreño, Arcesio (2020)
The aim of this study was to determine the relationship between the rickettsemia of A. marginale and environmental and genetic interactions in dual-purpose cattle in Arauca, Colombia. Blood samples were taken from 269 females from 14 farms, both in the dry and rainy seasons, and were analysed with the Wright and Hemacolor® techniques. The interaction between the presence of A. marginale with the variables breed type, season, age and parity was evaluated by analysis of variance. Resulted showed that 66.6% of positive animals to A. marginale were found in the dry season and 100% in the rainy season (p<0.001), presenting rickettsemia values between 0 and 0.14% (average: 0.04%). The rickettsia A. marginale showed interaction with the breed type (p<0.05), the creole animals and crosses of Brown Swiss x zebu and Simmental x zebu being more resistant, whereas Bos taurus animals were more susceptible. Age, parity number, body condition and season were not dependent on rickettsemia.